THE ASPECTS OF MODERN LINGUISTICS ANTHROPOLOGY IN SOUTH NIAS TRADITIONAL WEDDING CEREMONY - Adoramos Dakhi; Merdiana Tampubolon; Ismarini Hutabarat (LPPM Universitas Darma Agung, 2020)
The problems of the study were (1) what aspects of linguistics anthropology are found in South Nias traditional wedding ceremony? (2) how are the aspects of linguistics anthropology interconnected with South Nias traditional wedding ceremony?. This study found that (1) there were three aspects of linguistics anthropology in South Nias traditional wedding ceremony; they were performance, indexicality, and participation. (2)The three aspects found in South Nias traditional wedding ceremony were inseparable because they were interconnected strongly one another.